Collaboration between schools and museums for inclusive cultural education: Findings from the INARTdis-project - Gigerl, Monika; Sanahuja-Gavaldà, Josep M.; Petrinska-Labudovikj, Rozita; Moron-Velasco, Mar; Rojas-Pernia, Susana; Tragatschnig, Ulrich (Frontiers in Education, 2022)
The increasing heterogeneity in our communities is a reality and a foundational element of modern societies. This article deals with different aspects of political, social and cultural participation, processes of integration and inclusion. The aim of inclusion of all marginalized groups, among others integrating migrant communities, has to be a process of involving all sides—the local communities with publicly funded cultural institutions, the marginalized groups like migrant communities and the educational institutions in the local area. Therefore, the local community and schools have to be willing to make efforts in addressing interests and needs of all people, especially migrants or persons with disabilities. Cultural education as part of general education is based on a broad concept of culture and includes educational offers and processes in the context of different art disciplines. Participation in the field of culture is sought in the context of human rights as the right to live one's own culture as well as to participate in cultural life. Therefore, it is necessary to review cultural education offers within and outside the school context and to adapt them to the current population: Characteristics of differences such as first language, educational background, income or disability must be taken into account. This paper presents the findings of the data collection in the project INARTdis in the countries Austria, Spain, North Macedonia and Portugal. Firstly, educators from the school and extracurricular sector as well as people from the fields of culture were asked to answer the question: What is inclusive arts education and how can this be promoted through cooperation? The analysis of inclusive access to cultural institutions and arts education was conducted in 2021 using a mixed-method design. Secondly, during museum visits, results on the learners’ perspectives were collected. The aim was to find out what makes it easier for visitors to access the museum? The documentation of the visits was carried out according to the qualitative method Photovoice.